(untitled) (Journal of Partial Differential Equations, 1990)
In this paper, we decomposite the coefficient matrix of the Navier-Stokes equations with large parameter in &#955 power. By factor analysis and energy estimation, the long time existence and asymptotic expansion of the solution tor the system are obtained. Key words Navier-Stokes equations; expansion; approximation.